2015
DOI: 10.1007/s10903-015-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Social Status, Mental and Psychosocial Health, and Birth Weight Differences in Mexican–American and Mexican Immigrant Women

Abstract: Recent Mexican immigrant women on average have an unexpectedly low incidence of low birth weight (LBW). Birth weights decline and LBW incidence increases in post-immigrant generations. This pilot project tested the hypothesis that subjective social status (SSS) of pregnant women predicts variation in birth weight between Mexican immigrant and Mexican-American women. 300 low-income pregnant Mexican immigrant and Mexican-American women in South Texas were surveyed for SSS, depression, pregnancy-related anxiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…Although, local SSS was reduced in unemployed individuals and in individuals with lower income, there was no effect of local SSS on mental health. In contrast, prior research showed that local SSS was associated with mental health outcomes such as depressive symptoms4851 and perceived stress 52,53. One possible explanation for the result in this study could be that unemployed individuals tend to evaluate their position using objective status indices such as income and employment status.…”
Section: Discussioncontrasting
confidence: 88%
“…Although, local SSS was reduced in unemployed individuals and in individuals with lower income, there was no effect of local SSS on mental health. In contrast, prior research showed that local SSS was associated with mental health outcomes such as depressive symptoms4851 and perceived stress 52,53. One possible explanation for the result in this study could be that unemployed individuals tend to evaluate their position using objective status indices such as income and employment status.…”
Section: Discussioncontrasting
confidence: 88%
“…Higher subjective social status, as measured by the MacArthur Scale, increased the odds of having a baby with normal or higher birth weight in both Mexican American and Mexican immigrant women (Fleuriet and Sunil ). Subjective social status than other psychosocial variables was a better predictor in regression models of having a baby with normal or higher birth weight in both Mexican American and Mexican immigrant women (Fleuriet and Sunil ). Importantly, however, subjective social status was not significantly correlated with low birth weight in either group.…”
Section: Birth Weight and Cultural Understandings Of Pregnancy Among mentioning
confidence: 88%
“…Importantly, however, subjective social status was not significantly correlated with low birth weight in either group. This distinction is likely due to the statistically significant different correlations between subjective social status, depression, self‐esteem, perceived social stress, and pregnancy‐related anxiety in Mexican American and Mexican immigrant women (Fleuriet and Sunil , ). Specifically, subjective social status in Mexican American women correlated with each of the other psychosocial health variables, but it only correlated with self‐esteem in Mexican immigrant women.…”
Section: Birth Weight and Cultural Understandings Of Pregnancy Among mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on resilience among Latina women has often been framed as seeking explanations for the observed 'Latina Birth Paradox,' the observation that despite high average levels of poverty, low education and discrimination, Latina women, particularly first-generation immigrants, show low rates of adverse birth outcomes overall (Becerra et al, 1991;Fleuriet & Sunil, 2015). Previous quantitative researchers have considered social support, spirituality, strong family bonds, cross-border ties and living in ethnic enclaves as promoting resilience among pregnant Latina women (Bender & Castro, 2000;Hunter-Hernández et al, 2015;Perreira et al, 2018;de la Rosa et al, 2016;Torres et al, 2016).…”
Section: Research Determining How Communities and Individuals Survive Andmentioning
confidence: 99%